Malhas de amostragem retangular e hexagonal na geração de mapas de fertilidade e aplicação para agricultura de precisão - Schio, Leonice (2016)
Sample grid s are essential when we want to represent the variation in chemical and physical properties of the soil, being essential to know its features. In this way, this study aimed to relate the efficiency and practicality of using soil sampling knits of rectangular and hexagonal type in a farm located countryside Ivorá- RS. In order to get features that help the researcher and producer in choosing the appropriate mesh to represent and diagnose their crops by means of fertility maps and application. The methodological procedures consisted of structuring the rectangular and hexagonal sampling knits of 1 ha in the CR Campeiro 7, without user interference in the point s distribution. Soil samples were collected in June 2015. So, after analysis of the spatial distribution of points in the area for each of the cases the fertility maps and application were structured. Among the main results, it is noted that both knits can represent similarly the trends that the soil presents nevertheless, the rectangular grid, due to a higher number of points, can represent the variability more expressively, but was found that when there is a change in the position and number of sampling points in a crop, the representations of the maps have differences, which at first, analyzing only the fertility maps, these differences seem small, but when structured a map of application, this difference becomes significant as it will result in greater or lesser purchase of inputs. It is emphasized that each mesh has characteristics that will inevitably vary from crop to crop, and a sampling grid should be, always, planned and adjusted according to each case, combining the knowledge of the producer and additional data available to define the same.